Analysts' reputational concerns, self-censoring, and the international dispersion effect - Hwang, Chuan-Yang (2020)
Stocks with higher forecast dispersion earn lower future returns and have a greater upward bias in the mean reported earnings forecast in international markets. Both phenomena are stronger in countries with more transparent information environments, more developed stock markets, stronger investor protection, greater capital openness, and more intense usage of analysts' earnings forecasts. Using the 1997-1998 Asian financial crisis as a natural experiment, we find that both phenomena become weaker postcrisis in Malaysia, which imposed capital controls, relative to Thailand and South Korea, which opened their financial markets to foreigners. These results suggest that analysts in countries with greater demand for their forecasts and hence greater concerns for reputations are more likely to self-censor their low forecasts, which leads to a stronger dispersion-bias relation and a stronger dispersion effect.